2011
DOI: 10.1177/0020872811414598
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Amartya Sen’s human development perspectives to the fields of reproductive health and social work

Abstract: There is a significant lack of development studies on reproductive health, especially in developing countries. The field of social work has especially marginalized the study of reproductive health. Adding to this deficiency is the lack of meaningful theoretical frameworks guiding the reproductive field, especially in developing countries. This paper explores Amartya Sen’s theoretical perspectives as a possible theoretical framework that both guides the reproductive field and helps social work put reproductive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…Verschillende auteurs benadrukken dat de CA en het sociaal werk een wederkerige relatie hebben, hun normatieve uitgangspunten raken elkaar. Toch is er weinig empirisch materiaal over de manier waarop de CA het sociaal werk in de praktijk kan versterken (Den Braber, 2013;Jayasundara, 2011). In ons onderzoek toetsen we deze relatie door gebruik te maken van de CA als een analysekader om een sociaal werkpraktijk in India te evalueren.…”
Section: N T R O D U C T I Eunclassified
“…Verschillende auteurs benadrukken dat de CA en het sociaal werk een wederkerige relatie hebben, hun normatieve uitgangspunten raken elkaar. Toch is er weinig empirisch materiaal over de manier waarop de CA het sociaal werk in de praktijk kan versterken (Den Braber, 2013;Jayasundara, 2011). In ons onderzoek toetsen we deze relatie door gebruik te maken van de CA als een analysekader om een sociaal werkpraktijk in India te evalueren.…”
Section: N T R O D U C T I Eunclassified
“…that it is estimated that sexual and reproductive ill health accounts for one-third of the global burden of disease amongst women of reproductive age and one fifth of the burden of disease amongst the population overall. Echoing Blyth’s (2008) commentary, Jayasundara (2013) notes that reproductive health is marginalised both in the health agenda and also in the social work profession itself, claiming that it has never been a ‘mainstream social work area’ of focus, despite the many social and emotional issues arising for service-users (p. 135).…”
Section: Convergence Of Health and Social Outcomesmentioning
confidence: 99%
“…As a consequence of tensions about research-led practice, the evidence base for social work and health inequalities remains a work in progress. Differences in the emphasis and focus of social work practice can be identified in the global context of practice, for example, Jayasundara (2013) notes that where in the west health social workers might offer individual/couple counselling in specialist services like terminations of pregnancy or infertility, in developing countries social workers are more likely to be involved in community development initiatives rolling out family-planning programmes. In a preliminary review of published research in the UK auspiced by the Social Care Institute for Excellence (SCIE) that aimed to investigate evidence of effectiveness in reducing health inequalities, no studies were found which attempted to show that inequalities in health across the population were reduced (Coren et al, 2011).…”
Section: Education and Practitioner Research: The Widening Lensmentioning
confidence: 99%
“…Both the concept of human development, which emerged from the CA, and the IFSW (2014) definition of social work acknowledge the importance of social change and development towards cultivating the flourishing of human life and creating an enabling environment for people to enjoy their lives (Braber, 2013; Sen, 1999). This shared mission serves as a critical basis for the social work profession to explore the CA; however, of even greater relevance are the mutually reinforcing principles and the theoretical credibility that may be lent to key strategies and principles within social work practice (Braber, 2013; Jayasundara, 2011). In order to contribute effectively to the sustainable development movement, social work must re-examine not only its professional role, but also the knowledge base, strategies and actions that its practitioners may utilise to enact the professed values of social justice and self-determination.…”
Section: Social Work Engagement In Ca Discoursementioning
confidence: 99%
“…By expanding upon the traditional theoretical frameworks and drawing upon alternative knowledge bases, it is possible that social work may position itself as an effective agent for engaging in social change across multiple levels. The CA provides a strong theoretical lens for the re-examination of social justice within a social work and development context (Jayasundara, 2011; Sen, 1999).…”
Section: Social Work Engagement In Ca Discoursementioning
confidence: 99%